Faster postnatal decline in hepatic erythropoiesis than granulopoiesis in human newborns - Janovska, Petra; Bardova, Kristina; Prouzova, Zuzana; Irodenko, Ilaria; Kobets, Tatyana; Haasova, Eliska; Steiner Mrazova, Lenka; Stranecky, Viktor; Kmoch, Stanislav; Rossmeisl, Martin; Zouhar, Petr; Kopecky, Jan (Frontiers in Pediatrics, 2025)
BackgroundDuring human foetal development, the liver is the primary site of blood cell production, but this activity declines in the third trimester and postnatally as haematopoiesis shifts to bone marrow. In humans, this postnatal decline is not well characterized due to the scarcity of appropriate samples.ObjectiveTo characterize the effect of (i) gestational age at birth and (ii) length of survival after birth on hepatic haematopoiesis across various cell lineages involved.MethodsLiver autopsy samples from 25 born-alive infants, predominantly extremely preterm newborns who died mainly between 1 day and 3 weeks after birth, were analysed. Haematopoiesis was characterized using immunohistochemical staining of established cell type-specific protein markers. RNA-sequencing data from our previous study using the same samples were also explored.ResultsHaematopoiesis negatively correlates with both the duration of prenatal development and the length of postnatal survival. The effect of these two factors varies across different haematopoietic cell lineages. Prenatally and early postnatally, erythropoietic cells dominated hepatic haematopoiesis but were rapidly suppressed within three days after birth. Granulopoietic activity declined more gradually after birth. Analysis of the gene expression data revealed the possible involvement of several transcription factors in lineage-specific regulatory mechanisms.ConclusionThis study enhances our understanding of the postnatal decline of hepatic haematopoiesis in human newborns, highlighting the differential regulation of erythropoiesis and granulopoiesis after birth. These factors bring new in-depth knowledge about the biological processes critical for postnatal adaptation of human newborns.